Evaluation of the benefits of stem cell therapy in healing Anterior Cruciate Ligament (ACL) injuries - Khu, Adrian (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
PONV (Post Operative Nausea and Vomiting) or post-operative nausea and vomiting is a side effect that is often found after surgery and anesthesia. For patients, PONV is felt to be very disturbing, so PONV is called the big little problem. Factors related to PONV are patient factors, anesthesia factors, and surgical factors. Regarding surgical factors, the type of surgery that is at high risk for PONV is orthopedic surgery (22%). In addition, the relatively long duration of surgery and excessive surgical manipulation can also cause PONV in orthopedic surgery. To identify risk factors for PONV, a calculation for PONV has been developed. Based on research from (Donnerer, 2003), data from Koivuranta et al was combined with Apfel et al in developing this PONV risk score. The PONV risk score indicates that there are 4 (four) initial factors in determining PONV risk factors, namely female gender, history of PONV or motion sickness, history of not smoking, and history of using postoperative opioids to treat pain. Not only PONV risk factor scores for adult patients, there are also PONV risk factor scores for pediatric patients or Postoperative Vomiting in Children score. POVOC score is simplified as follows with the risk factor of duration of surgery 30 minutes, age 3 years, strabismus surgery, and positive history of PONV or motion sickness from parents or siblings. In preventing the occurrence of PONV, two approaches can be taken, namely a pharmacological approach and a non-pharmacological approach. The pharmacological approaches used are ondansetron and metoclopramide. Ondansetron is a 5-HT3 receptor antagonist. Whereas Metoclopramide inhibits dopamine (D2) receptors centrally and peripherally. This study aims to examine studies on the use of antiemetic drugs in preventing postoperative nausea and vomiting in orthopedic surgery patients at Rumkital in April 2023. The research was conducted in a cross-sectional-prospective manner and has been declared "ethically appropriate". The inclusion criteria for the research sample were patients undergoing orthopedic surgery who received antiemetic drug therapy as prophylaxis for postoperative nausea and vomiting in April 2023. From the results of research on orthopedic surgery patients who received antiemetic drug therapy as prophylaxis in preventing post-operative nausea and vomiting in accordance with the inclusion criteria, namely 31 patients, dominated by male patients (74.2%) with the highest age being 40 years (51.6%). Type of orthopedic surgery undertaken by Of the 31 patients, the largest were ORIF (19.4%) and Femur Column Fracture (ORIF) (19.4%). In this study, there were only 2 types of risk factors that patients had, namely 3 patients with a frequency of PONV who had 1 number of risk factors (history of not smoking) and as many as 3 patients with a frequency of PONV who also had 2 number of risk factors (female and history of not smoking). Meanwhile, the types of antiemetic drugs used were metoclopramide 10 mg IV (64.5%) and ondansetron 2 mg, 4 mg, and 8 mg IV (35.5%). The dose of antiemetic drug given and the time of administration to the patient are in accordance with literature recommendations. PONV only occurred in 9 patients (29%) of 31 orthopedic surgery patients in this study. Of the 9 patients, 8 patients used metoclopramide 10 mg IV and 1 patient used ondansetron 8 mg IV. This indicates that metoclopramide 10 mg IV is not effective in preventing PONV. Furthermore, 2 types of DRP were identified where one patient could experience more than one type of DRP. The DRP identified included drug side effects such as constipation, dizziness, chest pain, GI tract disorders and potential drug interactions, namely dexamethasone with ondansetron (9.7%) and tramadol with ondansetron (16.1%).